The dietary freeze-dried fruit powder of Actinidia arguta ameliorates dextran sulphate sodium-induced ulcerative colitis in mice by inhibiting the activation of MAPKs. Issue 9 (27th August 2019) - Lian, Lian; Zhang, Song; Yu, Zhenlong; Ge, Huiqi; Qi, Shizhou; Zhang, Xinxin; Long, Liping; Xiong, Xin; Chu, Donghai; Ma, Xiaochi; Li, Xianzhe; Gao, Huiyuan
Abstract : Oral administration freeze-dried Actinidia arguta powder could ameliorate ulcerative colitis disease via inhibiting the activation of MAPKs pathway. Abstract : In this study, we aimed at investigating the antiinflammatory activity of the freeze-dried fruit powder of Actinidia arguta (FAA) on dextran sulphate sodium (DSS)-induced ulcerative colitis (UC) in mice and the effect of its extract on lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages. For pharmacodynamic studies, the oral administration of FAA (300 or 600 mg kg −1 ) could decrease the disease activity index (DAI), reduce the incidence of colon and spleen edemas (caused by inflammation), and alleviate the pathological changes in UC. For research involving biochemical indicators, FAA could decrease the expression of inflammatory markers (such as myeloperoxidase (MPO)) and attenuate the oxidative stress levels. ELISA results revealed that the expressions of proinflammatory cytokines (IL-1β, IL-6, and TNF-α) were downregulated by FAA. Furthermore, the expression levels of the inflammation-induced activation of p38, JNK, and ERK were decreased by FAA. Hence, it was concluded that FAA could alleviate the UC symptoms in mice and the inflammatory response of macrophages via the MAPK signal pathway. Overall, FAA might have the potential to treat UC when used as a dietary supplement.